2013
DOI: 10.1371/journal.ppat.1003648
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Siglec-H in MCMV Infection Elevates Interferon Alpha Production but Does Not Enhance Viral Clearance

Abstract: Plasmacytoid dendritic cells (pDCs) express the I-type lectin receptor Siglec-H and produce interferon α (IFNα), a critical anti-viral cytokine during the acute phase of murine cytomegalovirus (MCMV) infection. The ligands and biological functions of Siglec-H still remain incompletely defined in vivo. Thus, we generated a novel bacterial artificial chromosome (BAC)-transgenic “pDCre” mouse which expresses Cre recombinase under the control of the Siglec-H promoter. By crossing these mice with a Rosa26 reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 59 publications
(82 reference statements)
4
45
0
Order By: Relevance
“…We found that SiglecH eGFP/eGFP mice had increased levels of systemic IFN-α compared to WT mice at 48 h p.i. (Figure 2E), similar to a recent study (11). Taken together, these data suggest that SiglecH deficiency does not affect IFN-I secretion by pDC in response to a synthetic TLR9 ligand or virus ex vivo but may influence IFN-I production by pDC during viral infection in vivo.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…We found that SiglecH eGFP/eGFP mice had increased levels of systemic IFN-α compared to WT mice at 48 h p.i. (Figure 2E), similar to a recent study (11). Taken together, these data suggest that SiglecH deficiency does not affect IFN-I secretion by pDC in response to a synthetic TLR9 ligand or virus ex vivo but may influence IFN-I production by pDC during viral infection in vivo.…”
Section: Resultssupporting
confidence: 91%
“…Corroborating these findings, SiglecH eGFP/eGFP mice also had slightly elevated levels of systemic IFN-α and proinflammatory cytokines compared to WT mice after HSV-1 infection (Figure 3A–C). These results are consistent with an immunomodulatory role for SiglecH in antiviral responses (6, 9, 11). To determine whether this effect was due to pDC, we bred CLEC4C-DTR Tg mice to SiglecH eGFP/+ and SiglecH eGFP/eGFP mice and infected them with HSV-1 in the presence or absence of pDC.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations